2017
DOI: 10.24966/ggm-8662/10015
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related-Changes-of-Trace-Element-Contents-in-Intact-Thyroid-of-Females-Investigated-by-Neutron-Activation-Analysis

Abstract: IntroductionThe endocrine organs, including the thyroid gland, undergo important functional changes during aging and a prevalence of thyroid dysfunction is higher in the elderly as compared to the younger population [1,2]. Advancing age is known to influence the formation of adenomatous goiter and thyroid cancer [3]. The prevalence of thyroid nodules is increased in the elderly, reaching a frequency of nearly 50% by the age of 65 [4]. Both prevalence and aggressiveness of thyroid cancer increase with age [2]. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The ratios of means and the difference between mean values of Br, Ca, Cl, I, K, Mg, Mn, and Na mass fractions in normal thyroid of females and males are presented in Table 4. Because, in our previous studies age-dependents of many ChE in thyroid gland was found [51][52][53][54], the comparison between ChE contents in thyroid of females and males separately in age group 1 and in age group 2 was also performed (Tables 5 & 6). The data of inter-correlation calculations (values of r -coefficient of correlation) including all ChE identified by us in thyroid of females and males separately are presented in Table 7.…”
Section: Resultsmentioning
confidence: 99%
“…The ratios of means and the difference between mean values of Br, Ca, Cl, I, K, Mg, Mn, and Na mass fractions in normal thyroid of females and males are presented in Table 4. Because, in our previous studies age-dependents of many ChE in thyroid gland was found [51][52][53][54], the comparison between ChE contents in thyroid of females and males separately in age group 1 and in age group 2 was also performed (Tables 5 & 6). The data of inter-correlation calculations (values of r -coefficient of correlation) including all ChE identified by us in thyroid of females and males separately are presented in Table 7.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, we found a significant age-related increase of Br content in human thyroid [25][26][27][28]31,32]. Therefore, a goitrogenic and, probably, carcinogenic effect of excessive Br levels in the thyroid of old females was assumed.…”
Section: Brominementioning
confidence: 90%
“…The content of Br, Ca, Cl, I, K, Mg, Mn, and Na were determined by INAA-SLR using a horizontal channel equipped with the pneumatic rabbit system of the WWR-c research nuclear reactor (Branch of Karpov Institute, Obninsk). Details of used neutron flux, nuclear reactions, radionuclides, gamma-energies, and spectrometric unit were presented in our earlier publications concerning the INAA-SLR of ChE contents in human thyroid, scalp hair, and prostate [27,28,[51][52][53] In a few days after INAA-SLR all thyroid samples were repacked separately in a high-purity aluminum foil washed with rectified alcohol beforehand and placed in a nitric acid-washed quartz ampoule and used for INAA-LLR. A vertical channel of the WWR-c research nuclear reactor (Branch of Karpov Institute, Obninsk).was applied to determine the content of Ag, Co, Cr, Fe, Hg, Rb, Sb, Sc, Se, and Zn by INAA-LLR.…”
Section: Sample Preparation and Methodsmentioning
confidence: 99%
See 2 more Smart Citations